2021
DOI: 10.3389/fimmu.2021.622599
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Analysis to Unravel Altered Genetic Pathways Underlying Early Onset and Late Onset Neonatal Sepsis. A Pilot Study

Abstract: Background: Neonatal sepsis is a systemic condition widely affecting preterm infants and characterized by pro-inflammatory and anti-inflammatory responses. However, its pathophysiology is not yet fully understood. Epigenetics regulates the immune system, and its alteration leads to the impaired immune response underlying sepsis. DNA methylation may contribute to sepsis-induced immunosuppression which, if persistent, will cause long-term adverse effects in neonates.Objective: To analyze the methylome of preterm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…Purified DNA was quantified with the fluorometric method (Quant-iT PicoGreen dsDNA Assay, Life Technologies, Carlsbad, CA, USA). Genome-wide methylation was assessed as previously described by Pozo-Lorente et al [21] using Infinium Human DNA Methylation EPIC 850 K arrays (Illumina Inc., San Diego, CA, USA) scanned on an Illumina HiScan SQ scanner (Illumina Inc., San Diego, CA, USA). The minfi R-package [22] was used to process and normalize the arrays [22,23].…”
Section: Estimation Of Immune Cell Compositionmentioning
confidence: 99%
“…Purified DNA was quantified with the fluorometric method (Quant-iT PicoGreen dsDNA Assay, Life Technologies, Carlsbad, CA, USA). Genome-wide methylation was assessed as previously described by Pozo-Lorente et al [21] using Infinium Human DNA Methylation EPIC 850 K arrays (Illumina Inc., San Diego, CA, USA) scanned on an Illumina HiScan SQ scanner (Illumina Inc., San Diego, CA, USA). The minfi R-package [22] was used to process and normalize the arrays [22,23].…”
Section: Estimation Of Immune Cell Compositionmentioning
confidence: 99%
“…Epigenetic alterations, especially changes in DNA methylation, have been found to be associated with a variety of diseases, including sepsis (7)(8)(9). Several studies have revealed differential methylation profiles which were correlated with sepsis status both in adults and neonates (10)(11)(12). Recently, we found that inhibiting DNA methylation by Decitabine can mitigate the effects of sepsis and improve survival of mice by attenuating the activation of NF-κB signaling pathway and down-regulating inflammatory cytokine levels.…”
Section: Introductionmentioning
confidence: 95%
“…Sepsis is associated with changes in DNA methylation patterns in blood leukocytes of critically ill patients, and the majority of the differentially methylated region-associated genes were differentially expressed ( 141 ). Functional analysis showed that these sepsis related alterations in DNA methylation involved inflammatory pathways participating in both the innate and adaptive immune response, as well as in cell adhesion and cell junctions ( 141 , 195 ). Likewise, the altered DNA methylation profiles in monocytes of septic patients correlated with increased IL-10 and IL-6 levels, as well as with organ dysfunction ( 143 ).…”
Section: Modification Of Dna Methylation Associated With Infectionmentioning
confidence: 99%